2017
DOI: 10.3390/healthcare5040085
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing Physical Activity for the Prevention and Treatment of Osteoporosis in Older Adults

Abstract: Osteoporosis is an age-related disease, characterised by low bone mineral density (BMD) and compromised bone geometry and microarchitecture, leading to reduced bone strength. Physical activity (PA) has potential as a therapy for osteoporosis, yet different modalities of PA have varying influences on bone health. This review explores current evidence for the benefits of PA, and targeted exercise regimes for the prevention and treatment of osteoporosis in older adults. In particular, the outcomes of intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
64
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(73 citation statements)
references
References 97 publications
5
64
0
4
Order By: Relevance
“…Implementing the TPB-based educational program augmented the scores of the construct of attitudes towards behavior at 6-months follow-up in the intervention group. This result is consistent with the ndings of Lachlan et al [32]. A clinical trial by Darker et al on walking improvement based on TPB reported a similar increase in individuals' attitudes towards PA [33].…”
Section: Discussionsupporting
confidence: 92%
“…Implementing the TPB-based educational program augmented the scores of the construct of attitudes towards behavior at 6-months follow-up in the intervention group. This result is consistent with the ndings of Lachlan et al [32]. A clinical trial by Darker et al on walking improvement based on TPB reported a similar increase in individuals' attitudes towards PA [33].…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, several studies [61][62][63] report that PA could also reduce the level of osteoporosis, resulting in a valid therapeutical approach for this disease in elderly people.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, about 20 million patients are prone to affecting osteoporotic VCFs [21]. The prevalence of VCFs in China increased from 15% in 50 years old to 36.6% among women aged 80 years or elderly [22,23]. VCFs would cause severe pain and confine spin activity and decrease quality of life.…”
Section: Discussionmentioning
confidence: 99%